Veteran Employment Lessons from the 100,000 Jobs Mission - Curry Hall, Kimberly (RAND Corporation, 2014)
Eleven companies cofounded the 100,000 Jobs Mission in 2011 to promote veteran employment. The coalition has grown to more than 175 member companies, representing almost every U.S. industry. These companies have hired more than 190,000 veterans as of September 2014, already far exceeding the original goal. RAND interviewed member companies to capture lessons and experiences and to identify further improvements to veteran employment opportunities.